Re-Thinking the Anthropological and Ethical Foundation of Economics and Business: Human Richness and Capabilities Enhancement - Giovanola, Benedetta (Journal of business ethics, 2009)
This article aims at showing the need for a sound ethical and anthropological foundation of economics and business, and argues the importance of a correct understanding of human values and human nature for the sake of economics and of businesses themselves. It is suggested that the ethical-anthropological side of economics and business can be grasped by taking Aristotle’s virtue ethics and Amartya Sen’s capability approach (CA) as major reference points. We hold that an “Aristotelian economics of virtues”, connected with the CA’s notion of human richness, can promote the shift to the concept of personhood, and can lead to a more “humanized” business, by fostering human flourishing, the enhancement of human capabilities, and the pursuit of a more humane development for each and every person.